Asset Management In The Perspective Of Islamic Interpretation And Economics: Study Of The Principle Of Balance In The World And The Hereafter - Femas Almuttaqin; Azriansyah; Prawira Wahyu Nugraha (Penerbit Hellow Pustaka, 2024)
Wealth management in Islam reflects the principle of balance between the interests of this world and the hereafter, which is an important basis for building a harmonious life. This research aims to examine the concept of wealth management from the perspective of Islamic interpretation and economics, with a focus on the values ​​of justice, halal and sustainability. The research method used is a qualitative approach with descriptive analysis of verses from the Koran, hadith, as well as classical and modern tafsir. The research results show that ideal wealth management according to Islam is not only oriented towards meeting material needs, but also towards social and spiritual welfare. It is hoped that these findings can contribute to the development of a balanced and applicable Islamic economic concept.